1985
DOI: 10.1007/bf00273860
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperprolactinaemia is associated with decreased insulin binding in vitro and insulin resistance in vivo

Abstract: We studied insulin receptor binding and carbohydrate metabolism in 10patients with severe hyperprolactinaemia and compared the findings with those obtained in 20 healthy control subjects. Insulin binding to monocytes and erythrocytes was significantly decreased in the patients with an excess of prolactin. Scatchard analysis of binding data indicated that a decrease in the number of receptors rather than in receptor affinity seems to be the prevailing cause of lowered binding in hyperprolactinaemic patients. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…According to other studies, IR in patients with hyperprolactinaemia is not associated with obesity nor with anthropometric parameters such as fat content, waist circumference, and bod mass index (BMI) [50]. Among humans the mechanism responsible for tissue IR in severe hyperprolactinaemia seems to be, at least in part, downregulation of insulin receptors [51]. The results of various studies suggest that in humans the effects of PRL may be complex or may vary depending on different conditions.…”
Section: Experimental Evidence Of the Relationship Between Hyperprola...mentioning
confidence: 98%
“…According to other studies, IR in patients with hyperprolactinaemia is not associated with obesity nor with anthropometric parameters such as fat content, waist circumference, and bod mass index (BMI) [50]. Among humans the mechanism responsible for tissue IR in severe hyperprolactinaemia seems to be, at least in part, downregulation of insulin receptors [51]. The results of various studies suggest that in humans the effects of PRL may be complex or may vary depending on different conditions.…”
Section: Experimental Evidence Of the Relationship Between Hyperprola...mentioning
confidence: 98%
“…Hypogonadism, particularly androgen deficiency, may further contribute to the development of the metabolic syndrome in hyperprolactinemia. It also acts peripherally, inducing insulin resistance [ 58 , 59 ] and dyslipidaemia [ 60 ]. Dissatisfaction with body composition and appearance may affect mood and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…32 It has been suggested that PRL also plays a role in modulating insulin sensitivity at adipose tissue by the regulation of adipose tissue markers, such as PPAR-γ, ADIPOQ and GLUT4. 33 However, both very high or low PRL levels impair βcell insulin-secretory capacity and insulin sensitivity, 21 inducing a downregulation of insulin receptors in case of severe hyperprolactinemia, 34 or resulting in visceral adipocyte hypertrophy when PRL levels are below the normal range. 35 In both cases, these mechanisms may lead to glucose intolerance and insulin resistance.…”
Section: Prolactin Effects On Pancreatic β-Cellsmentioning
confidence: 99%